AGING OUT OF THE FOSTER SYSTEM youths' perspectives. - Mosier-Puentes, Miranda; Diversi, Marcelo, 1967- ([S.l.] : ROUTLEDGE, 2024)
Decades of demographic studies and applied efforts have convinced scholars, students, and social workers that young people coming of age and transitioning out of the foster care system face great challenges in health, education, income, and general well-being. Despite the wealth of research on these outcomes, we know much less about the lived experiences of young people leaving foster care. Aging Out of the Foster System: Youths' Perspectives adds to this narrative the personal experiences of young people who are aging out or have aged out of their child welfare placement. The authors center the stories of these young people and apply critical ethnographic methods to frame their accounts with attention to the encounters within which they were produced, including power imbalances, institutional contexts, and relational dynamics. By centering the experiences of youths in these contexts and attending to the larger forces at work, this book helps connect the dots between youth aging out of the foster care system, social workers in Independent Living Programs, and the professors and scholars teaching the next generations of professionals working to support the aging out process.
Keywords: Child welfare; SOCIAL SCIENCE / Social Work; SOCIAL SCIENCE / Sociology / General